A Three-Step Heuristic Approach to the Electric Vehicle Path Planning Problem considering Charging - Shengping Yu; Yunfang Wang; Ruiyou Zhang; Junxiang Wang (Journal of Advanced Transportation)
With the rapid development of the electric vehicle industry, the problem of electric vehicle mileage limitation still exists. Recent studies focus on the minimum energy consumption path planning method or the charging route planning method, with a lack of studies considering midway charging scenarios. In this study, we propose a graph processing method for the electric vehicle, given the energy consumption and road conditions, and establish a mixed integer planning model for the electric vehicle path planning problem. The objective is the shortest time, with energy consumption as a constraint, aiming at the problem of shortest path planning for electric vehicles with midway charging. Taking into account real-time traffic information and energy consumption information related to road conditions, a three-step heuristic algorithm based on preprocessing traffic network, charging path planning, and subpath planning is proposed for the electric vehicle path planning problem. The simulation results show that the proposed method can determine optimal paths including charging stations and effectively alleviate electric vehicles’ “range anxiety” problem during medium- and long-distance travel.